Novel insight into the genetic diversity of strongylid nematodes infecting South-East and East Asian primates - Mason, Bethan; Cervena, Barbora; Frias, Liesbeth; Goossens, Benoit; Hasegawa, Hideo; Keuk, Kenneth; Langgeng, Abdullah; Majewski, Kasia; Matsumoto, Takashi; Matsuura, Keiko; Mendonça, Renata; Okamoto, Munehiro; et al. (Parasitology, 2024)
With many non-human primates (NHPs) showing continued population decline, there is an ongoing need to better understand their ecology and conservation threats. One such threat is the risk of disease, with various bacterial, viral and parasitic infections previously reported to have damaging consequences for NHP hosts. Strongylid nematodes are one of the most commonly reported parasitic infections in NHPs. Current knowledge of NHP strongylid infections is restricted by their typical occurrence as mixed infections of multiple genera, which are indistinguishable through traditional microscopic approaches. Here, modern metagenomics approaches were applied for insight into the genetic diversity of strongylid infections in South-East and East Asian NHPs. We hypothesized that strongylid nematodes occur in mixed communities of multiple taxa, dominated by Oesophagostomum, matching previous findings using single-specimen genetics. Utilizing the Illumina MiSeq platform, ITS-2 strongylid metabarcoding was applied to 90 samples from various wild NHPs occurring in Malaysian Borneo and Japan. A clear dominance of Oesophagostomum aculeatum was found, with almost all sequences assigned to this species. This study suggests that strongylid communities of Asian NHPs may be less species-rich than those in African NHPs, where multi-genera communities are reported. Such knowledge contributes baseline data, assisting with ongoing monitoring of health threats to NHPs.
Keywords: metagenomika; Strongylida; Oesophagostomum; Phylogeny; Japonsko; Primate Diseases; non-human primate; helminth; infekce hlísticemi řádu Strongylida; primáti; Metagenomics; zvířata; strongylida; nemoci opic; Japan; Strongylida Infections; orangutan; genetická variace; Genetic Variation; nemoci primátů; fylogeneze; metabarcoding; Animals; Borneo; Primates; Monkey Diseases